O dr. Milanu Jakliču in prvem prevodu Komunističnega manifesta v slovenskem jeziku - Perovšek, Jurij (Acta Histriae, 2020)
The first translation of the Communist Manifesto into Slovene was made by the lawyer dr. Milan Jaklič (Podgorica (Dobrepolje), 14 February 1886 - Ljubljana, 30 June 1963). Translation was published in 1908 by the publishing house of the newspaper Naprej, the newspaper of the Idrija district organization of the Yugoslav Social Democratic Party. Jaklič was among the most prominent members of the party. Before the First World War, he participated in the editorial board of its newspaper Zarja, and after the war became the political editor of her new newsletter Next. From the end of November 1919 until the beginning of March 1920 he acted as head of the provincial government's commission for Slovenia for social policy. At the end of May 1920 he became chief of the Ministry of social policy in Belgrade, and in 1923-1927 he was the director of the Central Office for workers' insurance in Zagreb. He then devoted himself as a private individual to research at in the field of agronomy. He was in Italian internment during World War II. After the war he lived in Vrhnika and in 1945-1962 worked part-time as a lawyer at Okrajno and then to the Local People's Committee of Vrhnika and in the municipality of Vrhnika. Jaklič's translation The communist manifesto was an integral part of the efforts of social democracy to ensure the systematic publication of socialist publications. He contributed to progress socialist press in Slovenia at the beginning of the 20th century.
Keywords: Jaklič, Milan; Jugoslovanska socialno-demokratska stranka; Komunistični manifest; slovenski pravniki; socializem; založba časopisa Naprej